Near Infrared Spectroscopy Monitoring in the Pediatric Cardiac Catheterization Laboratory. Issue 10 (10th January 2014) - Tanidir, Ibrahim Cansaran; Ozturk, Erkut; Ozyilmaz, Isa; Saygi, Murat; Kiplapinar, Neslihan; Haydin, Sertac; Guzeltas, Alper; Odemis, Ender
Abstract Near‐infrared spectroscopy (NIRS) is a noninvasive method used to evaluate tissue oxygenation. We evaluated the relationship between cerebral and renal NIRS parameters during transcatheter intervention and adverse events in the catheterization room. Between January 1 and May 31, 2012, 123 of 163 pediatric patients undergoing cardiac catheterization were followed by NIRS. All were monitored by electrocardiography, noninvasive blood pressure measurement, pulse oxymetry, initial and final blood lactate level measurement. The number of interventional procedures was 73 (59%). During the procedures, 39 patients experienced a total of 41 adverse events: 18 (19.5%) had desaturation, 10 (8.1%) arrhythmia, three (2.4%) had respiratory difficulty, six (4.8%) had a situation calling for cardiopulmonary resuscitation, three (2.4%) had anemia necessitating transfusion, and one (0.8%) had a cyanotic spell. Cranial NIRS values worsened in 12 (9.8%) and renal measurements worsened in 13 (12.5%) patients. The sensitivity and specificity of a 9% impairment of cranial values were 90 and 61%, respectively, while the corresponding calculations for a 21% fall in renal measurements were 54% sensitivity and 90% specificity. When arrhythmia developed, NIRS values fell simultaneously, while the development of a desaturation problem was heralded by NIRS falling 10–15 s earlier than changes in pulse oxymetry; on improving saturation, NIRS returned to earlier values 10–15 s before pulse oxymetry readings. NIRS monitoring may provide an early warning with regard to complications likely to develop during a procedure. A fall of 9% in cranial NIRS values, or of 21% in renal measurements, should raise clinician awareness.